ANALISIS COST-EFFECTIVENESS PENGGUNAAN SEFTRIAKSON DAN SEFOTAKSIM PADA TERAPI PROFILAKSIS APENDEKTOMI DI RS PKU MUHAMMADIYAH YOGYAKARTA TAHUN 2006-2007 - Muhartati, Sri Aisyah; Muhlis, Muh; Supadmi, Woro (Pharmaciana, 2011)
Cost-effectiveness analysis of ceftriaxone and cefotaxim prophylactic antibioticsof appendectomy in PKU Muhammadiyah Hospital Yogyakarta from January 2006 toDecember 2007 has been studied. This study was aimed to explore the direct medicalcost, cost-effectiveness ratio, and determine whether drugs of ceftriaxone or cefotaximwhose had more effective cost. This study was carried out by descriptive retrospectivedesign. The population was all inpatients of appendectomy getting prophylaxisantibiotics with either ceftriaxon or cefotaxim therapy in PKU MuhammadiyahHospital Yogyakarta. The population target were the appendectomy patients in thethird class of PKU Muhammadiyah Hospital Yogyakarta from January 2006 toDecember 2007. The result indicated that direct medical cost of the patients gettingceftriaxone therapy was Rp 422.257, whereas the cost of the patients getting cefotaximtherapy was Rp 487.680. Cost-effectiveness ratio of whom getting ceftriaxone therapywas Rp 105.564/day, whereas the ratio of whom getting cefotaxim therapy was Rp162.560. Finally, it have not been able to determine which drug is more cost-effective.